Greenhouse Evaporation Measuring Methods for Estimation of Reference Evapotranspiration - Sujitha, E.; Shanmugasundaram, K. (Recent Progress in Plant and Soil Research Vol. 1, 2021)
Due to the large area occupied by a Class A pan, various methods for estimating reference evapotranspiration (ETo) within greenhouses are used. Spatial changes influences, the depth of evapotranspiration. The research findings on what pan coefficient (Kp) should be used inside the greenhouse are inconclusive. As a result, the primary goal of the research was to compare ETo calculated by various methods within and outside of a greenhouse. A Class A pan (CAPi), a reduced pan (RPi60cm Ø) and a reduced pan (RPi20cm Ø) were installed inside a greenhouse, and another Class A pan (CAPo) was installed outside. ETo estimates, obtained by CAPi, RPi60cm Ø and RPi20cm Ø were 54%, 57% and 59% of those estimated by CAPo, respectively. A simple linear regression revealed positive coefficients R = 0.76 for the CAPo x CAPi, R = 0.96 for the CAPi and the RPi60cm Ø, R = 0.98 for the CAPi and the RPi 20cm Ø. For the specific conditions in this study, the utilization of a reduced pan as replacements for the class A pan is recommended to estimate ETo inside the greenhouse, as long as the equations adjusted in this experiment are utilized. The study found that reduced pans may be used to estimate ETo inside the greenhouse, and that replacing reduced pans would enhance the amount of area available for cultivation in the greenhouse.